In silico Evolutionary Divergence Analysis Suggests the Potentiality of Capsid Protein VP2 in Serotype-Independent Foot-and-Mouth Disease Virus Detection - Mishu, Israt Dilruba; Akter, Salma; Alam, A. S. M. Rubayet Ul; Hossain, M. Anwar; Sultana, Munawar (Frontiers in Veterinary Science, 2020)
Foot-and-mouth disease (FMD) is an economically devastating disease of the livestock worldwide and caused by the FMD virus (FMDV), which has seven immunologically distinct serotypes (O, A, Asia1, C, and SAT1–SAT3). Studies suggest that VP2 is relatively conserved among three surface-exposed capsid proteins (VP1–VP3) of FMDV, but the level of conservation has not yet been reported. Here we analyzed the comparative evolutionary divergence of VP2 and VP1 to determine the level of conservation in VP2 at different hierarchical levels of three FMDV serotypes (O, A, and Asia1) currently circulating in Asia through an in-depth computational analysis of 14 compiled datasets and designed a consensus VP2 protein that can be used for the development of a serotype-independent FMDV detection tool. The phylogenetic analysis clearly represented a significant level of conservation in VP2 over VP1 at each subgroup level. The protein variability analysis and mutational study showed the presence of 67.4% invariant amino acids in VP2, with the N-terminal end being highly conserved. Nine inter-serotypically conserved fragments located on VP2 have been identified, among which four sites showed promising antigenicity value and surface exposure. The designed 130 amino acid long consensus VP2 protein possessed six surface-exposed B cell epitopes, which suggests the possible potentiality of the protein for the development of a serotype-independent FMDV detection tool in Asia. Conclusively, this is the first study to report the comparative evolutionary divergence between VP2 and VP1, along with proposing the possible potentiality of a designed protein candidate in serotype-independent FMDV detection.